2012
DOI: 10.1016/j.biortech.2012.07.089
|View full text |Cite
|
Sign up to set email alerts
|

Early warning indicators for process failure due to organic overloading by rapeseed oil in one-stage continuously stirred tank reactor, sewage sludge and waste digesters

Abstract: Originally published as:Kleyböcker, A., Liebrich, M., Verstraete, W., Kraume, M., Würdemann, H. (2012) ABSTRACTEarly warning indicators for process failures were investigated to develop a reliable method to increase the production efficiency of biogas plants. Organic overloads by the excessive addition of rapeseed oil were used to provoke the decrease in the gas production rate. Besides typical monitoring parameters, as pH, methane and hydrogen contents, biogas production rate and concentrations of fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Kleyböcker et al [1] introduced three EWIs for overacidification in AD processes: EWI-VFA/Ca, EWI-PO 4 / Ca and EWI-PO 4 . The authors developed these indicators and demonstrated their predictive ability in an AD system with sewage sludge and rapeseed oil as substrates [1,26].…”
Section: Process Upset Indicatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kleyböcker et al [1] introduced three EWIs for overacidification in AD processes: EWI-VFA/Ca, EWI-PO 4 / Ca and EWI-PO 4 . The authors developed these indicators and demonstrated their predictive ability in an AD system with sewage sludge and rapeseed oil as substrates [1,26].…”
Section: Process Upset Indicatorsmentioning
confidence: 99%
“…The authors developed these indicators and demonstrated their predictive ability in an AD system with sewage sludge and rapeseed oil as substrates [1,26]. As other substrates rich in carbohydrates and low in grease are used as energy crop fed to AD plants, the verification of these indicators is important for these AD systems.…”
Section: Process Upset Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations